2003
DOI: 10.3177/jnsv.49.73
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of 1-Deoxy-D-Xylulose 5-Phosphate Synthase and Transketolase of Bacillus subtilis in Relation to Vitamin B6 Biosynthesis

Abstract: SummaryIn Escherichia coli, 4-(phosphohydroxy)-L-threonine and 1-deoxy-D-xylulose 5-phosphate are believed to be direct precursors of vitamin B6(B6), and 1-deoxy-D-xylulose 5-phosphate synthase (Dxs) and transketolase could catalyze the formation of each precur sor. In this report, the possible involvement Dxs and transketolase (Tkt) in B6 biosynthesis in Bacillus subtilis was investigated. The gene disruptant of tkt and conditional mutants of dxs were constructed, and their ability of B6 biosynthesis was exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
0
5
0
1
Order By: Relevance
“…Due to its wide substrate specificity the enzyme is involved in the catabolism of pentose sugars, in the formation of D-ribose 5-phosphate, and in the provision of D-erythrose 4-phosphate, a precursor of aromatic amino acids, aromatic vitamins, and pyridoxine (59). Since 4-(phosphohydroxy)-L-threonine and 1-deoxy-D-xylulose 5-phosphate are believed to be direct precursors of vitamin B6 in E. coli, and transketolase catalyses the formation of each precursor, vitamin B6 may be important for in vivo survival of APEC (57).…”
Section: Lipopolysaccharide (Lps) Contributes To Viability Of Apec Inmentioning
confidence: 99%
“…Due to its wide substrate specificity the enzyme is involved in the catabolism of pentose sugars, in the formation of D-ribose 5-phosphate, and in the provision of D-erythrose 4-phosphate, a precursor of aromatic amino acids, aromatic vitamins, and pyridoxine (59). Since 4-(phosphohydroxy)-L-threonine and 1-deoxy-D-xylulose 5-phosphate are believed to be direct precursors of vitamin B6 in E. coli, and transketolase catalyses the formation of each precursor, vitamin B6 may be important for in vivo survival of APEC (57).…”
Section: Lipopolysaccharide (Lps) Contributes To Viability Of Apec Inmentioning
confidence: 99%
“…Most bacteria that have pdxS-and pdxT-like genes have dxs orthologs, but no orthologs of dxs can be found in the genomes of archaea, Staphylococcus aureus, or Streptococcus pneumoniae, all of which apparently utilize the PdxST pathway (data not shown). Moreover, the B. subtilis conditional dxs mutant was not impaired in B 6 synthesis (32). Additionally, the five-carbon-containing compound utilized for PLP synthesis in yeast is derived from glucose as an intact unit (13); in contrast, 1-deoxy-D-xylulose-5-phosphate originates from condensation of pyruvate and glyceraldehyde 3-phosphate (9,15).…”
Section: Figmentioning
confidence: 99%
“…A conditional mutant of dxs (encoding 1 -deoxy-D-xylulose forming enzyme, 1-deoxy-D-xylulose synthase) was constructed, and its property was investi gated. As a result, we found that the dxs mutant pro duces the same amount of B6 as the wild-type B. subtilis (52). Therefore, it is likely that dxs is not involved in B6 biosynthesis.…”
Section: Status Of 1-deoxy-d-xylulose and 4-hydroxy-l-threomentioning
confidence: 48%
“…Transketo lase (tkt), which catalyzes the D-erythrose 4-phosphate forming reaction was disrupted in B. subtilis. The tkt dis ruptant did not show B6 auxotrophy, and produced a normal amount of B6, suggesting that tkt is not involved in B6 biosynthesis in B, subtilis (52). SerC gene, which is probably involved in 4-hydroxy-L-threonine forming route in E. coil, was also investigated.…”
Section: Status Of 1-deoxy-d-xylulose and 4-hydroxy-l-threomentioning
confidence: 99%